Effects of psychoeducational group interventions on peer rejection and aggression among children with conduct disorder - Salehi, Somaieh (2013)
Most of children with Conduct Disorder (CD), experience difficulties such as limited peer relationship and aggression. They have fewer opportunities to come along with non-aggressive peers and improve their social skills. These problems lead to negative outcomes for children with CD. The purpose of this study was to examine the effects of psychoeducational group interventions on peer rejection and aggression among children with CD. The research methodology used was true experimental design, under the design of randomized, pre-test, post-test, control group design. One hundred and thirty six children (boys and girls) between 8 to 10 year old with childhood onset type of CD selected from Centres under the license of rehabilitation administration and educational-vocational organization in Tehran, Iran. The instruments of this study include Peer Rejection Questionnaire (PRQ) and Child Behaviour Checklist (CBCL). This study conducted with four groups and three kinds of interventions include Making Choices Program (MCP - for children) for the first group, Barkley Behavioural Parent Training (BBPT) for the second group, and combination of MCP and BBPT for the third group. It is important to note that parents (mothers) of children in group two and three participated in the intervention of this study. Descriptive statistics and inferential statistics procedures were applied to answer the research questions concerning the effects of each intervention within the groups and between the groups on both peer rejection and aggression. Additionally, semistructured interview with three parents of each experimental group was conducted to confirm the quantitative findings and gain more understanding of the interventions. Overall, the Two-way Repeated Measure ANOVA was conducted to study the effects of groups across test. The results showed that the interaction between groups and test for peer rejection was significant. It means that the average of mean score for peer rejection across time (test) was significantly different among four groups (F (6, 264) = 1122.64, p < .05, η2= .962, f =5.03). Furthermore, the average of mean score for aggression across time (test) was significantly different among four groups (F (4.86, 213.80) = 1600.82, ƞ2= 0.99, f = 6.003). This study found that the effect for the combination of both MC program and BBPT was more than each program on peer rejection. However, the mean score of this variable remained permanent in the follow-up. Therefore, three kinds of psychoeducational group interventions in this study suggested for the peer rejection of children with Conduct Disorder. The other finding of this study was that combination of both MCP program and BBPT is more effective in post-test and follow-up compared with other interventions. The results of semi-structured interview presented that peer rejection and aggression of children with CD decreased after the intervention. It is recommended to conduct a global study on teachers; parents; parents and children; parents and teachers; and parents, teachers, and children to compare effectiveness of interventions on peer rejection and aggression of children with CD. In addition, it is suggested that another researcher conduct a qualitative research to gain more understanding of the effects of the interventions on peer rejection and aggression among children with CD.